An Analysis of Contextual Meaning in Olivia Rodrigo's Songs - Wijaya, Rivo Presti Roma; Rosita, Nur (Universitas Negeri Padang, 2023)
Contextual meaning is meaning that refers to context, or a sentence that can support the clarity of a meaning. This research was conducted to find the types of contextual meaning and changes in meaning in Olivia Rodridgo's songs entitled